Junius: including letters by the same writer, under other signatures (now first collected). To which are added, his confidential correspondence with [J.] Wilkes, and his private letters addressed to Mr. H.S. Woodfall. With a preliminary essay, notes, facsimiles, &c (Routledge, 1875)
With index.